(untitled) (Advances in Military Technology, 2019)
When working in a contaminated area while wearing individual protective equipment, there is a high risk of overheating and dehydration. In accordance with the valid documents of the Army of the Czech Republic, a person using protective equipment has to be provided with an adequate fluid intake. To perform the work, it is necessary to equip the soldier with a hydration device that is resistant to chemical warfare agents and is structured in a way that allows its use when means of personal protection or other equipment is used. The aim of the experimental work was to verify resistance of the construction materials of hydration devices and compare them. For comparison purposes, devices designed to provide resistance to chemical warfare agents and those that did not provide it were tested. To determine breakthrough times of selected materials, the MIKROTEST and the MINITEST methods were used.